Revisiting Islamic Studies: Cementing Bases for Integrating Science and Religion in Islamic Higher Educational Institutions - Muqowim, Muqowim; Lessy, Zulkipli (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
Transformation within Islamic State Higher Institutions (PTKI) from State College for Islamic Studies (IAIN) to State Islamic Universities (UIN) is a dynamically shifting paradigm in Islamic Studies. The transformation not only occurs formally administratively in infrastructures, curricula, or teaching approaches, but also in conceptual framework and knowledge paradigms. This research objective is to investigate whether Muslim academics need to review Islamic studies in higher Islamic education institutions to include science and to integrate it with Islamic studies both in curricula and methods of teaching. The method of this research is a rigorous literature based study focusing on reviewing previous studies related transformation that was held within the Islamic higher education institutions. The results show that in the transformation process within PTKIN, there is a meaningful shift of Islamic studies from traditional approaches to modern ones. Formerly, Islamic studies only associated with developing religious scripts (al-‘ulûm al-naqliyyah), while now it should focus also on developing logic and interpretation (al-‘ulûm al-‘aqliyyah). The change from the IAIN to the UIN is a concrete response toward an integrative relation between science and religion. Even though each UIN offers different concepts about the integrative paradigm designs, all UINs agreed on the importance of building a new tradition in the PTKIN with the integrative paradigms from theoretic-philosophic-concepts to practical-implemented-contexts.